1990
DOI: 10.1007/bf01888736
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography evaluation of radiolucent gallstones in vivo

Abstract: Computed tomography facilitates an in vivo classification of gallstones and can aid in the identification of calcifications that escape detection with conventional radiologic procedures. Of patients with radiolucent stones, 54.8% exhibited calcifications either in the form of discrete rims (41.9%) or at the center of the stone (12.9%). Densities of the noncalcified areas of partially calcified stones averaged 40.68 +/- 6.8 Hounsfield units (HU), which was not significantly higher than the average of 31.85 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Further, the stones analysed by us were obtained from patients who fulfilled all the conventional criteria for oral bile acid therapy. The reported proportion of radiolucent gallstones containing high amounts of calcium has varied from 10% (13) to 54.8% (14), with computed tomography providing higher yields (15,16).…”
Section: Discussionmentioning
confidence: 98%
“…Further, the stones analysed by us were obtained from patients who fulfilled all the conventional criteria for oral bile acid therapy. The reported proportion of radiolucent gallstones containing high amounts of calcium has varied from 10% (13) to 54.8% (14), with computed tomography providing higher yields (15,16).…”
Section: Discussionmentioning
confidence: 98%
“…12 Barakos et al reported that 21% of gallstones could not be detected by conventional CT. 22 Two in vitro studies also showed that 16% and 26% of gallstones were isoattenuating with bile, which always had a high cholesterol content. 23,24 Black pigment stones, which have a high affinity for calcium carbonate, have a high CT attenuation value while brown pigment stones, consisting mainly of calcium bilirubinate, have a relatively high attenuation although less than that of black pigment Values are mean Ϯ standard error of the mean. ALP, alkaline phosphatase; ALT, alanine transaminase; CBD, common bile duct; CRP, C-reactive protein ; GGT, g-glutamyltransferase; WBC, white cell count.…”
Section: Discussionmentioning
confidence: 99%
“…However, this potential drawback of UDCA is not supported by our clinical experience: in none of the 24 patients with C F associated liver disease could we document gallstone formation after periods of treatment as long as three years (unpublished observations). For future studies we would recommend measuring stone density by CT scanning before and after UDCA treatment (24).…”
Section: Discussionmentioning
confidence: 99%